(untitled) (Mustansiria Dental Journal, 2018)
The aim of this study is to estimate the severity of dental caries among dental school students. Dental caries severity was conducted among 19-23 years old students in all classes in Al- Mustansiria University / college of dentistry. The total sample composed of 150 students 30 students from each class (75 males total and 75 females total). Dental caries diagnosis was according to criteria of WHO(1). Results of the this study showed that none of the examined students were caries free; in another word, caries percentage was found to be 100%, DMFS values decrease with advancing class level with on significant difference between all classes and increase in Fs values with a significant difference between females in all classes this is attributed to the higher awareness regarding prevention of dental diseases among finish dental students.